Grounded Methodology: Recent Trends and Approaches - Sapkota, Mahendra (NPRC Journal of Multidisciplinary Research, 2025)
Grounded Theory (GT) has evolved significantly since its introduction in the 1960s by Glaser and Strauss, adapting to modern-day needs and implications in qualitative research. In this context, this paper follows a systematic review method and offers a critical approach. Grounded Theory was initially conceived to develop theories from empirical data, but these days, it includes heavily hybrid perspectives that add capabilities for interpretive praxis. In addition, processing large datasets with digital technologies has improved the complexity of analyzing data, which has a greater scope to capture and theorize within grounded methodology. The paper also discusses these evolutions and emphasizes that Grounded Theory has become diverse in both theory and practice, which calls for discovering and employing different tools and strategies. The paper concludes that a critical research gap exists in allowing truly universal, evidence-based theoretical models of grounded methods that can contribute to advanced social sciences research.